Perfil de fitocannabinoides en muestras derivadas al Laboratorio de control de calidad de la ENyS - Martins, Enrique Francisco Ludovico (2023)
Cannabis plants are classified into chemotypes, based on the relative concentrations of tetrahydrocannabinol (THC) and cannabidiol (CBD).Chemotype I has high THC content (sativa dominant); chemotype II has an approximate 1:1 content of THC:CBD (hybrid) and chemotype III hasCBD as the predominant constituent (indica dominant). Our aim was to classify the samples received at the ENyS Quality Control Laboratoryaccording to their chemotype. Cannabinoid analysis was performed using ultra-high-performance liquid chromatography coupled to massspectrometry and the THC/CBD ratio was calculated. 121 plant tissue samples were analyzed, which had a strong predominance ofchemotype I (75%) as well as 139 oil samples, wich rendered 41% chemotype I, 40% chemotype II and 19% chemotype III.